Ibn Bajja’s Noetic - Rachak, Jamal (Anales del Seminario de Historia de la Filosofía, 2009)
This paper aims at elaborating a very special topic relative to the medieval philosophy; particularly, the question of noetic as was dealt with by a philosopher of the Islamic occident. Although the article is but the first part of the whole work, it still reveals the originality and the innovative tendency brought about this philosopher. What is most essential in Ibn Bajja’s noetic is the absence of intellect in power and the presence of intellect in act, in the design of intellects, in addition the substance of the cogitative faculty is the intermediate spiritual forms. It is here where shows up the most important aspect of his originality; the forms which are closer to the nature of the intelligible, by virtue of the division into two parts: 1. By anteriority with regard to who/what resembles the sensible. 2. By posteriority with regard to who/what resembles the species/the kind.